Use of 3D ultrasound data sets to map the localised properties of fibre-reinforced composites - Smith, Robert A. (2010)
This thesis documents a programme of work undertaken from mid-2005 to mid-2009 as a part-time PhD, investigating the application of signal-processing methods to ultrasonic non-destructive evaluation (NDE) data from fibre-reinforced composite materials. The aims of the project were: